Layered negative plate and lithium ion battery thereof
By adopting a layered negative electrode sheet design in lithium-ion batteries, using the compounding ratio and content of different binders, the problem of electrode sheet cracking caused by volume expansion of silicon negative electrode materials is solved, and the cycle stability and electrochemical performance of the battery are improved. .
Patent Information
- Application Number
- CN202411390547.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-03
AI Technical Summary
The volume expansion of the silicon negative electrode material in lithium-ion batteries causes the electrode sheet to crack during charging and discharging, reducing cycle life and safety. The existing nanotechnology and composite material methods have problems with preparation complexity and stability.
The layered negative electrode sheet design is adopted to optimize the compounding ratio and content of different adhesives, combine the adhesives such as styrene acetic emulsion, EAA, PAA and SBR to form the first and second active layers to enhance the adhesion and machinery. Performance, reducing the risk of volume expansion and ductile rupture.
It improves the cycle stability and electrochemical performance of lithium-ion batteries, extends the battery life, avoids cracking of the pole sheet, and improves energy density and charge and discharge efficiency.
Smart Images

Figure BDA0005072286500000121 
Figure BDA0005072286500000131 
Figure HDA0005072286510000011
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrochemistry, and in particular relates to a layered negative electrode sheet and a lithium ion battery thereof. Background Art
[0002] Lithium-ion battery technology has become an indispensable power source for modern electronic devices. Its high energy density, excellent electrochemical performance and low self-discharge rate have made lithium-ion batteries widely used in portable electronic devices, power tools, electric vehicles and large-scale energy storage systems. With the rapid development of science and technology and economy, people have put forward higher requirements on the endurance of portable electronic devices, the power density of power tools, the mileage of electric vehicles and the energy storage efficiency of large-scale energy storage equipment. Therefore, the development of lithium-ion batteries with higher energy density, lower cost and longer service life has become an urgent task facing lithium-ion battery researchers and the industry.
[0003] In the development history of lithium-ion batteries, the selection and optimization of negative electrode materials have always been the focus of research. Although traditional graphite negative electrode materials have good cycle stability and high conductivity, their theoretical capacity is only 372mAh / g, which to a certain extent limits the further improvement of the energy density of lithium-ion batteries. In order to break through this bottleneck, researchers began to explore new negative electrode materials, among which silicon has attracted much attention due to its high capacity and high energy density.
[0004] Silicon anode materials have several potential advantages. First, the theoretical capacity of silicon is as high as 4200mAh / g, which is more than 11 times that of graphite, which means that in the same volume of battery, the use of silicon anode can store more charge, thereby providing longer battery life. Secondly, due to its high capacity, the silicon anode can achieve a higher energy density, allowing the battery to provide a longer battery life at the same size. In addition, the electrochemical potential of silicon is close to that of lithium, which helps to increase the voltage platform of the battery, thereby further improving the energy density of the battery.
[0005] However, despite the huge potential of silicon negative electrodes, they also face a key challenge in practical applications - the problem of volume expansion. At present, when preparing negative electrode sheets of lithium-ion batteries with a high silicon content (silicon materials account for more than 20% of the total active materials), silicon will undergo significant volume changes during the insertion (embedding) and removal (de-embedding) of lithium ions, and its volume change rate can reach 300%. This huge volume expansion causes the length and width of the negative electrode sheet when the battery is fully charged to increase by more than 4% compared to before charging, which is greater than the elongation at break of the copper foil current collector, causing the negative electrode sheet to crack, reducing the cycle life of the battery and even posing safety risks. Therefore, solving the problem of negative electrode sheet extension caused by the expansion of silicon negative electrodes is crucial to fully realizing the potential of silicon negative electrodes.
[0006] In order to solve the problem of volume expansion of silicon negative electrode, researchers have proposed a variety of strategies. One method is to design the microstructure of silicon negative electrode materials through nanotechnology, such as preparing nanowires, nanoparticles or nanoporous structures; these nanostructures can provide a larger surface area and more space to buffer volume changes, thereby reducing the damage to the electrode structure caused by expansion. Another method is to compound silicon with other materials, such as carbon materials, metal oxides or polymers, to form a composite material; the volume expansion of silicon is alleviated through the synergistic effect between materials. However, these methods still have some limitations. For example, the preparation of nanoporous structures may require template methods or self-assembly techniques. These technologies also face the challenges of long preparation cycles and high costs. In addition, the ions and solvent molecules in the electrolyte under high voltage or high temperature conditions are easy to react with the surface of the nanomaterial, resulting in damage to the surface structure of the material. The overall structural stability of the negative electrode sheet decreases, resulting in poor ductility during charging and discharging and increased risk of rupture. When silicon is compounded with other materials, the uniformity and stability of the composite material are difficult to guarantee, and the preparation process is difficult. Especially in large-scale production, failure to fully mix or form a tight bonding interface may lead to structural changes or phase changes during the embedding and extraction of ions, resulting in cracking or falling off of the electrode during subsequent processing and use.
[0007] Therefore, the preparation and research of a silicon-containing negative electrode sheet with excellent cycle stability and high energy density is of great significance to the development of lithium-ion batteries. Summary of the invention
[0008] In view of the problems in the prior art, the present invention discloses a layered negative electrode sheet and a lithium ion battery thereof. The negative electrode sheet of the present invention adopts a layered design, and by optimizing and balancing the compounding ratio and content of different binders in the layered active layer, the problem of electrode sheet cracking caused by volume expansion of the silicon negative electrode during charging and discharging is effectively solved, thereby improving the cycle stability and electrochemical performance of the battery.
[0009] The present invention is achieved through the following technical solutions:
[0010] In a first aspect, the present invention provides a layered negative electrode sheet, the layered negative electrode sheet comprising a current collector layer and a layered active layer coated on at least one side of the current collector layer; the layered active layer is sequentially a first active layer and a second active layer on at least one side of the current collector layer; the first active layer contains a first active material, a first binder material, a first dispersant material and a first conductive material; the second active layer contains a second active material, a second binder material, a second dispersant material and a second conductive material;
[0011] The first binder material includes two types: styrene-acrylate emulsion (styrene-acrylic emulsion for short) and ethylene acrylic acid copolymer emulsion (EAA for short); the second binder material includes two types: polyacrylic acid copolymer (PAA for short) and polystyrene-butadiene copolymer (SBR for short); wherein, the mass ratio A of styrene-acrylic emulsion and EAA is selected from 0.3≤A≤3, and the mass ratio B of PAA and SBR is selected from 0.3≤B≤4; the mass of the first binder material accounts for 1%-10% of the total mass of the first active layer, and the mass of the second binder material accounts for 2%-10% of the total mass of the second active layer.
[0012] The present invention aims at the volume expansion and ductile fracture problems of silicon-based negative electrode sheets during charge and discharge, and proposes a layered negative electrode sheet. The active layer of the structure uses binders of different types and ratios. Styrene acrylic emulsion and EAA composite binder are used on the side close to the current collector to enhance the bonding force between the active material and the current collector and reduce the concentration of cohesive force; PAA and SBR composite binder are used on the side away from the current collector to improve mechanical properties and bonding, inhibit rebound, and enhance structural stability. By optimizing the content and ratio of the two binders, the synergistic effect of the binders is achieved, ensuring the stability of the negative electrode sheet structure, reducing volume expansion, improving ductility, avoiding cracking, and improving the capacity and cycle stability of the battery.
[0013] As a further solution, the glass transition temperature of the styrene acrylic emulsion ranges from -40°C to -60°C, the glass transition temperature of the EAA ranges from 30°C to 50°C, the glass transition temperature of the PAA ranges from 100°C to 130°C, and the glass transition temperature of the SBR ranges from -20°C to 20°C. The glass transition temperature within a certain range can be obtained by varying the degree of cross-linking of polymer chains between different active layer binder molecules, thereby better adapting to temperature changes during battery charging and discharging and maintaining the stability of the negative electrode sheet structure.
[0014] As a further solution, the thickness of the first active layer is selected from 30-100 μm, the thickness of the second active layer is selected from 30-100 μm, and the thickness ratio D of the first active material layer to the second active material layer is selected from 0.75≤D≤1.25.
[0015] By optimizing the thickness ratio and adhesion of the layered active layer, the battery's charge and discharge efficiency, mechanical strength, and cycle stability can be improved.
[0016] Furthermore, the thickness of the first active layer is selected from 50-70 μm, and the thickness of the second active layer is selected from 50-70 μm, wherein the thickness ratio D of the first active material layer to the second active material layer is preferably D=1.
[0017] As a further solution, the polyacrylic acid copolymer includes one or a combination of polyacrylic acid, polyacrylamide, polyacrylonitrile, and polyacrylate; polyacrylic acid copolymer provides excellent mechanical stability and crack resistance during battery charging and discharging due to its excellent adhesion, high glass transition temperature and low swelling rate, which helps to improve battery efficiency and extend service life.
[0018] As a further solution, the first active material and the second active material each independently include a silicon-based material and a carbon material; wherein the silicon-based material includes a silicon oxide material (SiO x , x is the number of oxygen in the silicon oxide material), one or more of silicon metal oxide materials and silicon carbon materials; the carbon material includes one or more of graphite, soft carbon and hard carbon; the mass of silicon-based materials accounts for more than 20% of the total mass of active materials.
[0019] As a further embodiment, the first dispersant material and the second dispersant material are independently selected from one or more of sodium carboxymethyl cellulose, polyvinyl pyrrolidone, polymethyl methacrylate, and polyethylene glycol octylphenyl ether.
[0020] As a further solution, the first conductive agent material and the second conductive agent material are independently selected from one or more of carbon blacks such as acetylene black and conductive carbon black; conductive polymers such as carbon nanotubes, graphene, graphite, polyaniline, polythiophene, etc.; metal oxide conductive agents such as tin oxide and zinc oxide; and carbon nanofiber conductive agents.
[0021] As a further solution, the current collector layer is selected from a metal current collector layer; as some specific examples: the metal current collector layer includes one or more of a copper foil current collector layer, an aluminum foil current collector layer, and a nickel foil current collector layer.
[0022] As a further solution, the proportion of the first active material in the total mass of the first active layer is selected from 85-97%; the proportion of the second active material in the total mass of the second active layer is selected from 85-95%; the appropriate active material ratio ensures a high load and an increase in battery energy density. At the same time, a high proportion of active materials means that they can participate in the reaction more effectively during charging and discharging, thereby improving battery efficiency.
[0023] As a further solution, the proportion of the first conductive agent material to the total mass of the first active layer is selected from 0.2-3%; the proportion of the second conductive agent material to the total mass of the second active layer is selected from 0.2-3%; an appropriate amount of conductive agent can improve the conductivity of the battery, reduce internal resistance, and enhance charging and discharging efficiency. It helps to form an efficient conductive network, ensure smooth movement of electrons, and reduce energy loss. Evenly distributed conductive agents can also prevent the formation of hot spots and improve thermal stability.
[0024] As a further solution, the proportion of the first dispersant material to the total mass of the first active layer is selected from 0.2-3%; the proportion of the second dispersant material to the total mass of the second active layer is selected from 0.2-3%; an appropriate dispersant ratio helps to evenly distribute the active substance, binder and conductive agent in the active layer, prevent agglomeration, and reduce the shedding of active substances during battery charging and discharging, thereby extending the battery life.
[0025] In a second aspect, the present invention provides a lithium ion battery, wherein the lithium ion battery comprises the layered negative electrode sheet described in the first aspect.
[0026] The characteristics and beneficial effects of the present invention are as follows: the present invention adopts a layered negative electrode sheet design, and uses binders of different types and contents in the layered active layer of the negative electrode sheet. On the one hand, a styrene acrylic emulsion and EAA compound are used as the binder of the first active layer close to the current collector side, and the characteristics of high viscosity and high flexibility are fully utilized when compounded, reducing the cohesive force of the active layer, reducing the risk of cohesive force concentration and pole piece extension. On the other hand, the use of PAA and SBR compound as a binder in the second active layer away from the current collector side can provide better mechanical properties and high adhesion, inhibit pole piece rebound, improve pole piece ductility, maintain pole piece structural stability, so as to adapt to the volume change of the battery during the charging and discharging process, and by optimizing the content and compounding ratio of the first and second binders in the active layer, the synergistic effect can be fully utilized, thereby improving the battery capacity and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0028] Figure 1 This is a plan view of the negative electrode sheet of the battery provided in Example 1 DETAILED DESCRIPTION
[0029] In order to facilitate the understanding of the present invention, the present invention will be described in more detail below, and embodiments of the present invention are given, but the scope of the present invention is not limited thereby.
[0030] In a first aspect, the present invention provides a layered negative electrode sheet, the layered negative electrode sheet comprising a current collector layer and a layered active layer coated on at least one side of the current collector layer; the layered active layer is sequentially a first active layer and a second active layer on at least one side of the current collector layer; the first active layer contains a first active material, a first binder material, a first dispersant material and a first conductive material; the second active layer contains a second active material, a second binder material, a second dispersant material and a second conductive material;
[0031] The first binder material includes two types: styrene-acrylate emulsion (styrene-acrylic emulsion for short) and ethylene acrylic acid copolymer emulsion (EAA for short); the second binder material includes two types: polyacrylic acid copolymer (PAA for short) and polystyrene-butadiene copolymer (SBR for short); wherein, the mass ratio A of styrene-acrylic emulsion and EAA is selected from 0.3≤A≤3, and the mass ratio B of PAA and SBR is selected from 0.3≤B≤4; the mass of the first binder material accounts for 1%-10% of the total mass of the first active layer, and the mass of the second binder material accounts for 2%-10% of the total mass of the second active layer.
[0032] The present invention aims to solve the problems that silicon-based negative electrode sheets expand in volume during battery charging and discharging, are easily ductile and fractured, and thus affect battery capacity and cycle stability. The present invention provides a layered negative electrode sheet, in which the layered active layers of the negative electrode sheet use binders of different types and contents. On the one hand, by using a compound of styrene acrylic emulsion and EAA as the active layer binder close to the current collector, the high flexibility of styrene acrylic emulsion and the excellent bonding performance of EAA can be used to enhance the bonding force between the active material and the current collector; this is because the presence of ethylene and acrylic acid units in EAA gives it high bonding and good coating function, and condenses with metal ions on the current collector surface to form strong chemical bonds, which is more conducive to stable bonding with the current collector layer; and styrene acrylic emulsion also contains relatively rigid benzene rings and flexible segments of acrylate groups, which enable it to maintain good flexibility, which is conducive to the close bonding of the internal structure of the battery and the dispersion of cohesive force when the pole piece expands, maintaining interface stability, and at the same time EAA and styrene acrylic emulsion contain similar segment components, so they have strong molecular bonding force to form a tight bond, so that when used in compound, they can give full play to the characteristics of high viscosity and high flexibility, reduce the cohesive force of the active layer, and reduce the risk of cohesive force concentration and pole piece extension when the active material expands.
[0033] On the other hand, by using a combination of PAA and SBR as a binder in the active layer on the side away from the current collector, better mechanical properties and high adhesion can be provided, the pole piece rebound can be suppressed, the pole piece ductility can be improved, the adhesion with the active layer on the side close to the current collector can be enhanced, and the pole piece structure can be maintained stable to adapt to the volume change of the battery during the charge and discharge process. This is because the segment structure and polar groups of PAA can form a strong hydrogen bond with the surface of the active material, and SBR can form a stable bonding network between the active materials. The combination of the two substances has a dual effect to improve the bonding force and stability between the active layers; in addition, the block composition structure of SBR makes it highly elastic and has excellent crack resistance. While PAA provides high viscosity to enhance cohesion and improve the mechanical strength of the material, its high elasticity can effectively absorb and alleviate the stress concentration phenomenon generated by the active material during the charge and discharge process. The dual composite effect can improve the stability of the pole piece structure and suppress the pole piece rebound. In addition, the polar groups contained in PAA and SBR have good affinity, which can also improve the compatibility between the electrode and the electrolyte, promote the penetration and adsorption of the electrolyte, and help the uniform distribution of the electrolyte, thereby improving the charge and discharge performance of the battery.
[0034] In addition, the PAA binder used in the second active layer and the EAA binder in the first active layer have similar acrylic structures, which can effectively penetrate each other at the molecular level, further enhancing the interfacial bonding strength between the layered active layers, making the transmission path of electrons and ions smoother, effectively reducing the internal resistance of the battery, improving the capacity and rate performance of the battery, further maintaining the stability of the electrode structure, and preventing the electrode from cracking and falling off.
[0035] In addition, the present invention also regulates and optimizes the content of the first binder and the second binder in the active layer and their respective compounding ratios. The appropriate compounding ratio of the binder and the appropriate proportion of the binder in the active layer can better exert a synergistic effect and fully balance its adhesion and flexibility, thereby ensuring the stable existence between the negative electrode sheet structures while reducing the volume expansion of the electrode sheet during the charging and discharging process, improving the ductility of the negative electrode sheet and avoiding cracking of the negative electrode sheet; thereby improving the battery capacity and cycle stability.
[0036] As a further solution, the glass transition temperature range of the styrene acrylic emulsion is -40°C to -60°C, the glass transition temperature range of the EAA is 30°C to 50°C; the glass transition temperature range of the PAA is 100°C to 130°C, and the glass transition temperature range of the SBR is -20°C to 20°C.
[0037] As a further solution, the thickness of the first active layer is selected from 30-100 μm, the thickness of the second active layer is selected from 30-100 μm, and the thickness ratio D of the first active material layer to the second active material layer is selected from 0.75≤D≤1.25.
[0038] The appropriate thickness of the active layer can ensure a good contact area between the layered active layers and between the active material and the current collector, improve the adhesion, maintain the stability of the pole sheet structure, and thus improve the charge and discharge efficiency of the battery; if the active layer is too thin, it is not conducive to the improvement of energy density, and the uneven density of the coating surface during the coating of the negative electrode sheet will also affect the stability of the active layer; if the active layer is too thick, it will hinder the electrolyte from penetrating evenly and effectively into the current collector layer, and may also cause the expansion rate and elongation rate of the pole sheet to increase, which is not conducive to the improvement of the performance of the pole sheet. At the same time, by adjusting the thickness ratio of the active layer, it is ensured that the active layer close to the current collector has a higher flexibility, thereby reducing the cohesive force; while the active layer away from the current collector improves the mechanical strength by enhancing the cohesive force, effectively suppressing the rebound effect of the negative electrode sheet. In this way, the synergistic effect between the compound binders can be better exerted to achieve a good balance between the two; the ductility of the overall structure of the negative electrode sheet is improved, and the risk of the negative electrode sheet falling off and rupture caused by the volume expansion of the negative electrode sheet during the charge and discharge cycle of the negative electrode sheet is reduced, and the capacity and cycle stability of the battery are further improved.
[0039] Furthermore, the thickness of the first active layer is selected from 50-70 μm, and the thickness of the second active layer is selected from 50-70 μm, wherein the thickness ratio D of the first active material layer to the second active material layer is preferably D=1.
[0040] As a further solution, the polyacrylic acid copolymer includes one or a combination of polyacrylic acid, polyacrylamide, polyacrylonitrile, and polyacrylate; these types of polyacrylic acid copolymers have good bonding properties, high glass transition temperatures, and low swelling rates, thereby providing good mechanical stability and crack resistance during battery charging and discharging; and the low swelling rate can ensure that the expansion of the negative electrode sheet is suppressed when it contacts the electrolyte, thereby improving the battery's charging and discharging efficiency and cycle stability, and extending the battery's service life.
[0041] As a further solution, the first active material and the second active material each independently include a silicon-based material and a carbon material; wherein the silicon-based material includes a silicon oxide material (SiO x , x is the number of oxygen in the silicon oxide material), one or more of silicon metal oxide materials and silicon carbon materials; the carbon material includes one or more of graphite, soft carbon and hard carbon; the mass of silicon-based materials accounts for more than 20% of the total mass of active materials.
[0042] As a further embodiment, the first dispersant material and the second dispersant material are independently selected from one or more of sodium carboxymethyl cellulose, polyvinyl pyrrolidone, polymethyl methacrylate, and polyethylene glycol octylphenyl ether.
[0043] As a further solution, the first conductive agent material and the second conductive agent material are independently selected from one or more of carbon blacks such as acetylene black and conductive carbon black; conductive polymers such as carbon nanotubes, graphene, graphite, polyaniline, polythiophene, etc.; metal oxide conductive agents such as tin oxide and zinc oxide; and carbon nanofiber conductive agents.
[0044] As a further solution, the current collector layer is selected from a metal current collector layer; as some specific examples: the metal current collector layer includes one or more of a copper foil current collector layer, an aluminum foil current collector layer, and a nickel foil current collector layer.
[0045] As a further solution, the proportion of the first active material in the total mass of the first active layer is selected from 85-97%; the proportion of the second active material in the total mass of the second active layer is selected from 85-95%; the proportion of active material in the appropriate range can ensure that the active layer has a higher active material loading, thereby improving the energy density of the battery. At the same time, the high proportion of active material also means that during the charge and discharge process, the active material can more effectively participate in the electrochemical reaction, thereby improving the charge and discharge efficiency of the battery; in addition, the optimization range of the above-mentioned binder of the present invention can also ensure that the active layer can still maintain excellent adhesion and stability under high load, and effectively inhibit cracks and shedding caused by changes in the volume of the pole piece.
[0046] As a further solution, the proportion of the first conductive agent material to the total mass of the first active layer is selected from 0.2-3%; the proportion of the second conductive agent material to the total mass of the second active layer is selected from 0.2-3%; the conductive agent material ratio in a suitable range can ensure that the active layer has good conductivity, thereby reducing the internal resistance of the battery and increasing the charge and discharge rate. The appropriate addition of the conductive agent can form an effective conductive network, allowing electrons to be smoothly transferred between active materials, reducing energy loss during charge transfer. In addition, the uniform distribution of the conductive agent helps to reduce the generation of local hot spots, thereby improving the thermal stability of the battery.
[0047] As a further solution, the proportion of the first dispersant material to the total mass of the first active layer is selected from 0.2-3%; the proportion of the second dispersant material to the total mass of the second active layer is selected from 0.2-3%; the dispersant material ratio in a suitable range can ensure that the active material, binder and conductive agent in the active layer are evenly dispersed to avoid the occurrence of agglomeration; in addition, the dispersant can also inhibit the shedding of the active material during the battery charging and discharging process, thereby extending the service life of the battery.
[0048] In a second aspect, the present invention provides a lithium ion battery, wherein the lithium ion battery comprises the layered negative electrode sheet described in the first aspect.
[0049] As a specific example of the implementation of the present invention, the detailed case is provided as follows:
[0050] Example 1
[0051] Preparation of active material: A mixture of 80% graphite and 20% silicon-carbon material is selected as the active material, wherein 80% is the percentage of the weight of the graphite material in the total weight of the active material; 20% is the percentage of the weight of the silicon-carbon material in the total weight of the active material.
[0052] Preparation of the first active layer: 0.6% by mass of carbon black conductive agent (SP), 0.2% by mass of carbon nanotube conductive agent (CNT), 1.2% by mass of carboxymethyl cellulose (CMC), 2% by mass of styrene acrylic emulsion binder (glass transition temperature of -50°C), and 2% by mass of ethylene acrylic acid copolymer (glass transition temperature of 40°C) binder are used, and mixed with active material materials at a mass ratio of 94%. The mass ratio of the above materials is the proportion of the mass of the materials used to the total mass of the first active layer. After the above materials are accurately weighed, they are fully mixed by a mixer and then dispersed in an appropriate amount of deionized water to form a stable first active layer slurry.
[0053] Preparation of the second active layer: Use carbon black conductive agent (SP) with a mass ratio of 0.6%, carbon nanotube conductive agent (CNT) with a mass ratio of 0.2%, carboxymethyl cellulose (CMC) with a mass ratio of 0.2%, polystyrene-butadiene copolymer (glass transition temperature of 0°C) (SBR) with a mass ratio of 2.5%, polyacrylic acid-polyacrylonitrile and polyacrylamide copolymer binder (glass transition temperature of 125°C) with a mass ratio of 2.5%, and mix with active material materials at a mass ratio of 94%. The mass ratio of the above materials is the proportion of the mass of the materials used to the total mass of the second active layer. After accurately weighing the above materials, mix them thoroughly and evenly with a mixer, and then disperse them in an appropriate amount of deionized water to form a stable second active layer slurry.
[0054] Coating process: A double-layer coater is selected, equipped with a double-die coating head extrusion coating device, and the first active layer slurry and the second active layer slurry are placed in the two material troughs of the coater respectively. Copper foil is used as the negative electrode current collector layer and fixed on the conveyor belt of the coater. Start the coater and control the two coating heads at the same time. The first active layer slurry is first evenly coated on one side of the negative electrode current collector to form a first active layer with a thickness of 50μm. The coating and drying temperature is 80℃, the speed is 2m / min, and the oven length is 15m. Then the second active layer slurry is coated on the first active layer to form a second active layer with a thickness of 50μm. After coating one surface of the current collector, repeat the coating on the other side of the current collector in the above manner. After coating, the negative electrode sheet is sent to the oven for drying. The oven temperature is 100℃ and the treatment time is 10h to remove moisture and solidify the binder to form a stable layered structure.
[0055] Subsequent processing: After the negative electrode sheet is completely dried, subsequent processing steps such as cutting and slitting are carried out to make negative electrode sheets that meet the requirements of battery assembly.
[0056] Example 2
[0057] The specific preparation method is the same as that of Example 1, except that: in the first active layer, the mass proportion of the styrene acrylic emulsion binder is 4.1%, the mass proportion of the ethylene acrylic acid copolymer binder is 1.9%, and the mass proportion of the active material is 92%; in the second active layer, the mass proportion of the polyacrylic acid-polyacrylonitrile and polyacrylamide copolymer binder is 2%, and the mass proportion of the polystyrene-butadiene copolymer (SBR) is 2%; that is, A=2.15, B=1
[0058] Example 3
[0059] The specific preparation method is the same as that in Example 1, except that: in the first active layer, the styrene acrylic emulsion binder accounts for 3% by weight, the ethylene acrylic acid copolymer binder accounts for 2% by weight, and the active material accounts for 93% by weight; in the second active layer, the polyacrylic acid-polyacrylonitrile and polyacrylamide copolymer binder accounts for 2% by weight, and the polystyrene-butadiene copolymer (SBR) accounts for 2% by weight; that is, A=1.5, B=1
[0060] Example 4
[0061] The specific preparation method is the same as that in Example 1, except that: in the first active layer, the mass proportion of the styrene acrylic emulsion binder is 2.7%, the mass proportion of the ethylene acrylic acid copolymer binder is 1.3%, the mass proportion of the polyacrylic acid-polyacrylonitrile and polyacrylamide copolymer binder in the second active layer is 5.2%, the mass proportion of the polystyrene-butadiene copolymer (SBR) is 1.8%, and the mass proportion of the active material is 92%; that is, A=2, B=2.9
[0062] Example 5
[0063] The specific preparation method is the same as that of Example 1, except that: the mass proportion of the styrene acrylic emulsion binder in the first active layer is 1.5%, the mass proportion of the ethylene acrylic acid copolymer binder is 2.5%, the mass proportion of the polyacrylic acid-polyacrylonitrile and polyacrylamide copolymer binder in the second active layer is 2.5%, and the mass proportion of the polystyrene-butadiene copolymer (SBR) is 2.5%; that is, A=0.6, B=1
[0064] Example 6
[0065] The specific preparation method is the same as that in Example 1, except that: the mass proportion of the styrene acrylic emulsion binder in the first active layer is 1%, the mass proportion of the ethylene acrylic acid copolymer binder is 3%, the mass proportion of the polyacrylic acid-polyacrylonitrile and polyacrylamide copolymer binder in the second active layer is 1.9%, and the mass proportion of the polystyrene-butadiene copolymer (SBR) is 3.1%; that is, A=0.6, B=0.6
[0066] Example 7
[0067] The specific preparation method is the same as that of Example 1, except that the thickness of the first active layer is 80 μm, and the thickness of the second active layer is 100 μm.
[0068] Example 8
[0069] The specific preparation method is the same as that of Example 1, except that the thickness of the first active layer is 80 μm, and the thickness of the second active layer is 73 μm.
[0070] Comparative Example 1
[0071] The specific preparation method is the same as that in Example 1, except that only one active layer is prepared, and the carbon black conductive agent (SP) accounts for 0.6% by mass, the carbon nanotube conductive agent (CNT) accounts for 0.2% by mass, the carboxymethyl cellulose (CMC) accounts for 1.2% by mass, the styrene-acrylic emulsion binder accounts for 1% by mass, the ethylene acrylic acid copolymer binder accounts for 1% by mass, the polystyrene-butadiene copolymer (SBR) accounts for 1%, and the polyacrylic acid-polyacrylonitrile and polyacrylamide copolymer binder accounts for 1% by mass and is mixed with the active material at a mass ratio of 94%. The mass ratio of the above materials is the ratio of the mass of the materials used to the total mass of the active layer. After the above materials are accurately weighed, they are fully mixed by a blender and then dispersed in an appropriate amount of deionized water to form a stable active layer slurry.
[0072] Comparative Example 2
[0073] The specific preparation method is the same as that of Example 1, except that the second active layer is coated on one side of the surface of the negative electrode current collector, and the first active layer is coated on the surface of the second active layer.
[0074] Comparative Example 3
[0075] The specific preparation method is the same as that in Example 1, the difference is that the first active layer uses 0.6% by mass of carbon black conductive agent (SP), 0.2% by mass of carbon nanotube conductive agent (CNT), 1.2% by mass of carboxymethyl cellulose (CMC), and 3% by mass of styrene acrylic emulsion binder, which are mixed with 95% by mass of active material.
[0076] Comparative Example 4
[0077] The specific preparation method is the same as that in Example 1, the difference is that the second active layer uses 0.6% by mass of carbon black conductive agent (SP), 0.2% by mass of carbon nanotube conductive agent (CNT), 0.2% by mass of carboxymethyl cellulose (CMC), and 3% by mass of polyacrylic acid-polyacrylonitrile and polyacrylamide copolymer binder, which are mixed with 96% by mass of active material.
[0078] Comparative Example 5
[0079] The specific preparation method is the same as that of Example 1, except that in the first active layer, the styrene acrylic emulsion binder accounts for 3.2% by weight and the ethylene acrylic acid copolymer binder accounts for 0.8% by weight.
[0080] Comparative Example 6
[0081] The specific preparation method is the same as that in Example 1, the difference is that the second active layer uses 0.8% by mass of carbon black conductive agent (SP), 1% by mass of carbon nanotube conductive agent (CNT), 1% by mass of carboxymethyl cellulose (CMC), 0.7% by mass of polystyrene-butadiene copolymer (SBR), and 3.5% by mass of polyacrylic acid-polyacrylonitrile and polyacrylamide copolymer binder, which are mixed with 93% by mass of active material.
[0082] Comparative Example 7
[0083] The specific preparation method is the same as that of Example 1, except that in the first active layer, the styrene acrylic emulsion binder accounts for 8% by weight, the ethylene acrylic acid copolymer binder accounts for 8% by weight, and the active material accounts for 82% by weight.
[0084] Comparative Example 8
[0085] The specific preparation method is the same as that of Example 1, except that the thickness ratio D of the first active layer to the second active layer is selected from D=2.
[0086] Specific test conditions and methods
[0087] Preparation of positive electrode sheet: prepare positive electrode slurry according to the mass ratio of positive electrode active material: conductive agent SP: PVDF: NMP of 95:2:3:100, apply it on aluminum foil and dry it to prepare positive electrode sheet, and bake the positive electrode sheet in a vacuum oven at 100°C;
[0088] Diaphragm: Use polyethylene (PE) diaphragm;
[0089] Electrolyte: The electrolyte is a 1 mol / L LiPF6 solution, and the solvent is composed of EC (ethylene carbonate) and DEC (diethyl carbonate) in a volume ratio of 1:1;
[0090] Assembly: The above-mentioned positive electrode sheet, negative electrode sheet, electrolyte and separator are assembled into a lithium-ion soft-pack battery according to the lithium-ion battery assembly requirements.
[0091] Related battery characteristics test:
[0092] The elongation of the negative electrode sheet in length and width after the battery is fully charged:
[0093] Lengthwise elongation = (full charge negative electrode sheet length - negative electrode sheet length before injection) / negative electrode sheet length before injection * 100%
[0094] Width direction elongation = (full charge negative electrode sheet width - negative electrode sheet width before injection) / negative electrode sheet width before injection * 100%
[0095] Confirm the cracking of the negative electrode edge after the battery is fully charged: Confirm whether it is cracked
[0096] The expansion rate of the negative electrode in the thickness direction after the battery is fully charged:
[0097] Thickness expansion rate = (thickness of negative electrode sheet after full charge of battery - thickness of negative electrode sheet after rolling) / thickness of negative electrode sheet after rolling * 100%
[0098] 0.5C cycle performance test:
[0099] The battery was placed at 25°C and cycled at 0.5C current in the charge and discharge voltage range of 2.8-4.2V. The initial capacity was recorded as Q0, and the capacity after 50 cycles was recorded as Q1. The capacity retention rate after 200 cycles at 0.5C was calculated by the following formula:
[0100] 0.5C cycle 200 cycles capacity retention rate (%) = Q1 / Q0×100%.
[0101] Rate charging performance test:
[0102] The battery was placed at 25°C, discharged at 0.33C to 2.8V, and charged to 4.2V at 0.5C and 2C respectively. The charging capacity at 0.5C was recorded as C0, and the charging capacity at 2C was recorded as C1. The capacity retention rate at different charging rates was calculated by the following formula:
[0103] Example: 2C capacity retention rate (%) = C1 / C0×100%
[0104] Table 1
[0105]
[0106]
[0107] It can be seen from the data in Table 1 that Examples 1-8 have better electrochemical performance than Comparative Examples 1-8, and the expansion rate and elongation rate of the fully charged negative electrode sheets are both low, and no cracking occurs; this illustrates that the layered negative electrode sheets provided in the present invention and the use of a specific type and ratio of binders can effectively improve the cycle stability and rate performance of the battery; and it has a significant improvement effect on solving the problems of volume expansion and electrode elongation and cracking of silicon-based negative electrode sheets during the charge and discharge process in the prior art.
[0108] It can be seen from Examples 1-8 and Comparative Example 1 that, relative to Examples 1-8, Comparative Example 1 adopts a method of directly mixing four binders to prepare an active layer. During the battery charge and discharge test after the electrode is assembled, the elongation is too large, and the electrode has obvious edge cracks, resulting in the battery's cycle stability and capacity retention rate being worse than those of Examples 1-8. This shows that when the four binders are mixed to prepare an active layer, the coordination effect of the four binders' performance cannot be fully balanced, resulting in uneven distribution of cohesive force, which is not conducive to maintaining interface stability, affecting the bonding effect with the current collector layer, thereby increasing the risk of electrode rupture, resulting in poor capacity and charge and discharge rate performance during the electrode cycle.
[0109] It can be seen from Examples 1-8 and Comparative Example 2 that in Comparative Example 2, the active layer containing PAA and SBR binders is placed on the side close to the current collector, and the active layer containing styrene acrylic emulsion and EAA binder is coated thereon as the side away from the current collector; although the two active layers have good adhesion, the high elasticity and excellent crack resistance of PAA and SBR binders when used in combination cannot be fully utilized as the outermost layer to inhibit the rebound of the electrode, resulting in a large volume expansion and extension of the electrode during the charge and discharge cycle, and its condensation ability and flexibility with the surface of the current collector are lower than the compounding effect of styrene acrylic emulsion and EAA, and it is easy to crack during the charge and discharge process of the electrode; and styrene acrylic emulsion and EAA binder are in contact with the electrolyte as the outermost layer, and their compatibility with the electrolyte is lower than the compounding effect of PAA and SBR binders, which is not conducive to promoting the penetration and adsorption of the electrolyte, reducing the charge and discharge efficiency of the battery, and affecting the cycle stability and capacity retention rate of the battery.
[0110] Through Example 1, Comparative Example 3 and Comparative Example 4, it can be found that the negative electrode sheet prepared by using the compound of PAA and SBR and the compound of styrene acrylic emulsion and EAA as the active layer binder in the layered negative electrode sheet of Example 1 respectively has better electrochemical performance and electrode sheet stability during the battery charge and discharge cycle test than the negative electrode sheet prepared by using one binder in the active layer in Comparative Example 3 and Comparative Example 4; this shows that the compound use of two binders in the active layer has a good synergistic effect. In Comparative Example 3, only the styrene acrylic emulsion binder is used as the binder of the first active layer and is coated on the side close to the current collector. Although it has good flexibility, it can disperse the cohesive force when the electrode sheet expands. , but its bonding force to the current collector is poor, which is not conducive to the stable bonding of the current collector layer. It is easy to fall off during the battery cycle, causing the pole piece to expand, thereby reducing the battery capacity and rate performance; while in Comparative Example 4, only polyacrylic acid-polyacrylonitrile and polyacrylamide copolymer binders are used as active layer binders away from the current collector side. Although it has good bonding stability with the first active layer, it cannot well suppress the pole piece rebound during the charge and discharge process in contact with the electrolyte, and provide stable mechanical properties to maintain the stability of the pole piece structure; causing the pole piece to have excessive elongation during the cycle process, cracking, and then affecting the battery cycle life and capacity retention rate. And lacking the synergistic effect of SBR, the compatibility of its second active layer with the electrolyte is reduced, and the electrolyte cannot be fully transmitted and penetrated, resulting in the general performance of the battery as a whole.
[0111] Through Examples 1-8 and Comparative Examples 5 and 6, it can be found that the appropriate amount of binder compounding ratio in Examples 1-8 can give full play to the synergistic effect of the binder, and has a good effect on improving the expansion and cracking of the pole piece and increasing the battery rate and capacity; while in Comparative Example 5, the mass ratio of the styrene acrylic emulsion binder to the EAA binder is too large, which has high flexibility and fully disperses the cohesive force, but is not convenient for fully utilizing the excellent bonding performance of EAA, resulting in reduced adhesion to the collector layer, and the pole piece is easy to fall off during the cycle, thereby increasing the pole piece elongation rate and reducing the battery rate and capacity; similarly, when we performed charge and discharge tests on Comparative Example 6, similar unfavorable factors were found. In Comparative Example 6, the mass ratio of the polyacrylic acid-polyacrylonitrile and polyacrylamide copolymer binders was too large, lacking sufficient SBR synergistic effect, resulting in the second active layer as the side away from the current collector in contact with the electrolyte, suppressing the rebound of the pole piece layer, and providing sufficient mechanical properties to maintain the stability of the pole piece. The effect is poor, which leads to the pole piece being easy to cause expansion and cracking during the charge and discharge process, and ultimately affecting the electrochemical performance of the battery.
[0112] It can be seen from Examples 1-8 and Comparative Example 7 that an appropriate amount of active layer additives is conducive to obtaining good electrochemical performance of the battery during the charge and discharge process, and can fully play a role in improving problems such as expansion and cracking of the pole piece; when the binder of the first active layer in Comparative Example 7 is significantly excessive relative to Examples 1-8 of the present invention, its electrochemical performance is also significantly reduced, which can be explained that excessive addition of binder in the first active layer is prone to cause the styrene-acrylic emulsion binder and ethylene acrylic acid copolymer to agglomerate, resulting in an increase in the internal resistance of the battery, and the electrolyte wettability will also deteriorate, occupying the space of the active material in the active layer, reducing the transmission efficiency of lithium ions, and thus affecting the capacity and rate performance of the battery. While Examples 1-8 use the compound content of styrene-acrylic emulsion binder and ethylene acrylic acid copolymer within the optimized range, and the appropriate proportion fully improves the battery charge and discharge rate, and obtains better electrochemical performance and pole piece stability.
[0113] It can be seen from Examples 1-8 and Comparative Example 8 that the thickness of the first active layer in Comparative Example 8 is twice the thickness of the second active layer, and the pole piece obviously cracks during the battery charge and discharge cycle, and the expansion rate and elongation rate are relatively high; this is because when the thickness of the first active layer exceeds a certain range relative to the thickness of the second active layer, the effect of the second active layer in suppressing the expansion rebound of the pole piece will be reduced, and the pole piece is prone to cracking, and it is not conducive to the full penetration and diffusion of the electrolyte to the current collector layer, reducing the migration efficiency of lithium ions, thereby resulting in a reduction in the charge and discharge rate and capacity of the battery, and failing to obtain good electrochemical performance.
[0114] It can be found from Examples 1, 2, 3, 4 and Examples 5 and 6 that the binder compounding ratio within the preferred range can achieve the best synergistic effect; it can be seen from Examples 1, 2, 3 and Example 5 that when the amount of styrene acrylic emulsion binder added in the first active layer is slightly more than that of EAA binder within the optimized range, the elongation of the pole piece in the length direction is within 1.6%, and the capacity cycle retention rate is above 90%; it can be seen from Examples 1, 4 and 6 that when the amount of polyacrylic acid-polyacrylonitrile and polyacrylamide copolymer binder added in the second active layer is slightly more than that of SBR binder within the optimized range, the elongation of the pole piece in the width direction is within 1.7%, and the capacity cycle retention rate is above 90%; it indicates that further regulating and optimizing the binder compounding ratio within the optimized range of the present invention can obtain full play of the synergistic performance of the binder, which is of great significance for inhibiting pole piece cracking, improving the elongation and expansion rate of the pole piece during charging and discharging, and improving the electrochemical performance.
[0115] Through Examples 1, 2, 3, 4, 5, 6 and Examples 7, 8, it can be found that the thickness of the first active layer and the second active layer within the preferred range is conducive to obtaining the best effect of suppressing the expansion of the electrode, and the elongation and expansion rate are low, thereby having a higher capacity and rate performance, which has a significant effect on improving the overall electrochemical performance of the battery.
[0116] It should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A layered negative electrode sheet, comprising a current collector layer and a layered active layer coated on at least one side of the current collector layer; the layered active layer is sequentially a first active layer and a second active layer on at least one side of the current collector layer; the first active layer contains a first active material, a first binder material, a first dispersant material and a first conductive material; the second active layer contains a second active material, a second binder material, a second dispersant material and a second conductive material; The first binder material includes two types: styrene-acrylate emulsion and ethylene acrylic acid copolymer emulsion; the second binder material includes two types: polyacrylic acid copolymer and polystyrene-butadiene copolymer; wherein, The mass ratio A of styrene-acrylate emulsion and ethylene acrylic acid copolymer emulsion is selected from 0.3≤A≤3, and the mass ratio B of polyacrylic acid copolymer and polystyrene-butadiene copolymer is selected from 0.3≤B≤4; the mass of the first binder material accounts for 1%-10% of the total mass of the first active layer, and the mass of the second binder material accounts for 2%-10% of the total mass of the second active layer.
2. The layered negative electrode sheet according to claim 1, characterized in that: The glass transition temperature range of the styrene-acrylate emulsion is -40°C to -60°C, and the glass transition temperature range of the ethylene acrylic acid copolymer emulsion is 30°C to 50°C; the glass transition temperature range of the polyacrylic acid copolymer is 100°C to 130°C, and the glass transition temperature range of the polystyrene-butadiene copolymer is -20°C to 20°C.
3. The layered negative electrode sheet according to claim 1, characterized in that: The thickness of the first active layer is selected from 30-100 μm, the thickness of the second active layer is selected from 30-100 μm, wherein the thickness ratio D of the first active material layer to the second active material layer is selected from 0.75≤D≤1.25; Furthermore, the thickness of the first active layer is selected from 50-70 μm, and the thickness of the second active layer is selected from 50-70 μm, wherein the thickness ratio D of the first active material layer to the second active material layer is preferably D=1.
4. The layered negative electrode sheet according to claim 1, characterized in that: The polyacrylic acid copolymers include one or a combination of polyacrylic acid, polyacrylamide, polyacrylonitrile and polyacrylate.
5. The layered negative electrode sheet according to claim 1, characterized in that: The first active material and the second active material each independently include a silicon-based material and a carbon material; wherein the silicon-based material includes a silicon oxide material (SiO x , x is the number of oxygen in the silicon oxide material), one or more of silicon metal oxide materials and silicon carbon materials; the carbon material includes one or more of graphite, soft carbon and hard carbon; the mass of silicon-based materials accounts for more than 20% of the total mass of active materials.
6. The layered negative electrode sheet according to claim 1, characterized in that: The first dispersant material and the second dispersant material are independently selected from one or more of sodium carboxymethyl cellulose, polyvinyl pyrrolidone, polymethyl methacrylate, and polyethylene glycol octylphenyl ether; the first conductive agent material and the second conductive agent material are independently selected from one or more of carbon black such as acetylene black and conductive carbon black; conductive polymers such as carbon nanotubes, graphene, graphite, polyaniline, and polythiophene; metal oxide conductive agents such as tin oxide and zinc oxide, and carbon nanofiber conductive agents; the current collector layer is selected from a metal current collector layer.
7. The layered negative electrode sheet according to claim 1, characterized in that: The proportion of the first active material to the total mass of the first active layer is selected from 85-97%; the proportion of the second active material to the total mass of the second active layer is selected from 85-95%.
8. The layered negative electrode sheet according to claim 1, characterized in that: The proportion of the first conductive material to the total mass of the first active layer is selected from 0.2-3%; the proportion of the second conductive material to the total mass of the second active layer is selected from 0.2-3%.
9. The layered negative electrode sheet according to claim 1, characterized in that: The proportion of the first dispersant material to the total mass of the first active layer is selected from 0.2-3%; the proportion of the second dispersant material to the total mass of the second active layer is selected from 0.2-3%.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the layered negative electrode sheet according to any one of claims 1 to 9.
Citation Information
Cited By
Sodium ion battery negative plate, battery and preparation method
CN121331763A
